Intervention with Young Mexicans in Conflict with the Law Based on Community Psychology - Corchado Vargas, Ángel (Pensando Psicología, 2016)
Purpose: To describe the activities that have been carried out in the context of the application of the community psychology model to Mexican youth (called “Juvenile Offenders”) who, for various reasons, have been referred to the so-called juvenile detention centers, located in the state of Mexico, in the metropolitan area of Mexico. Topic: Awareness of the activities that have been carried out with juvenile offenders will prospectively allow to design increasingly relevant intervention strategies for the population concerned based on community social psychology.Development: At first, some considerations on how psychology students from the School of Higher Studies (FES by its Spanish acronym) Iztacala, UNAM, are trained in the field of research are discussed and then the manner in which an effective intervention with Mexican juvenile offenders can be made is presented. The various interventions that have been made in juvenile detention centers are listed, as well as the methodology used, showing the progress of such intervention and proposals for improvement in the work carried out by psychology students from the Universidad Nacional Autónoma de México, FES Iztacala.Conclusions: It is expected that this model will serve to train students in similar scenarios in Latin America, considering ethical relevance and social commitment to the social sphere, as well as deductive and inductive dynamics involved in the research-intervention process.
Keywords: social commitment; juvenile offenders; juvenile detention centers; community psychology